Plasma proteomic changes during therapeutic hypothermia in resuscitated patients after cardiac arrest - Oda, Teiji (Exp Ther Med, 2019)
Hypothermia is used for several h during cardiac and aortic surgery to protect ischemic organs. Therapeutic hypothermia (TH) is used for ≤24 h as a treatment for comatose patients after the return of spontaneous circulation (ROSC) following cardiac arrest. The proteomic approach may provide unbiased data on alterations in the abundance of proteins during TH. The objective of this study was to assess the effects of cooling/rewarming on the plasma proteome during TH after ROSC and to identify the mechanism underlying its therapeutic effects. A total of nine comatose adult patients, resuscitated shortly after cardiac arrest, were cooled to 34°C for 24 h and slowly rewarmed to 36°C. A quantitative gel-free proteomic analysis was performed using the isobaric tag for relative and absolute quantification labeling tandem mass spectrometry. Plasma samples were obtained prior to cooling and rewarming, and immediately after rewarming, from all patients during TH after ROSC. A total of 92 high-confidence proteins were identified. Statistically significant alterations were observed (>1.2-fold increase or <0.833-fold decrease) in the levels of 15 of those proteins (P=0.003–0.047), mainly proteins belonging to the acute-phase response or platelet degranulation. Unexpectedly, the levels of free hemoglobin (hemoglobin subunits α and β) were significantly downregulated during TH (P<0.05). The level of the terminal complement complex (SC5b-9) showed significant reduction after cooling (P=0.023). Although the acute-phase response proteins were upregulated, the abundance of complement proteins did not change, and the levels of SC5b-9 and free hemoglobin decreased during TH in patients after ROSC.